Pengaruh Sikap Pada Media Pembelajaran Daring dan Etos Kerja Terhadap Kinerja - Alvin Setiawan; Ribhan Ribhan (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
This study aims to determine the effect of: (1) attitudes towards online learning media technology on the performance of private high school teachers in Metro City, (2) work ethic on the performance of private high school teachers in Metro City who teach online during the covid-19 pandemic. This research is a causal comparative research with a quantitative approach. The population of this research are teachers who work in private high schools in Metro City. The samples taken in this study were four private high schools located in Metro City, totaling 113 people. Data was collected by using a questionnaire method which has been tested for validity and reliability. The data analysis technique used is multiple regression. The results showed that: (1) attitudes to online learning media technology had a positive and significant effect on teacher performance at private high schools in Metro City. (2) work ethic has a positive effect on the performance of private high school teachers in Metro City.